Blood pressure abnormalities in children with sickle cell anemia. Issue 3 (5th November 2013) - Becker, Amy M.; Goldberg, Jordan H.; Henson, Michael; Ahn, Chul; Tong, Liyue; Baum, Michel; Buchanan, George R.
Abstract Background Kidney disease is an important cause of morbidity and mortality in patients with sickle cell anemia (SCA). The factors that affect progression of renal disease are unknown, especially in children and adolescents. Alterations in blood pressure, including hypertension and lack of the normal nocturnal dip in blood pressure, are important determinants of diabetic nephropathy and other renal diseases and may play a role in sickle cell nephropathy. Our primary hypothesis was that children with SCA who have microalbuminuria will demonstrate less nocturnal dipping of blood pressure compared to patients without microalbuminuria. We also investigated other potential factors associated with microalbuminuria. Procedure This prospective study of 52 adolescents with SCA followed in the Children's Medical Center Dallas Comprehensive Sickle Cell Center characterized 24‐hour ambulatory blood pressure profiles and presence of microalbuminuria. Stepwise logistic regression was performed to identify significant independent factors that are associated with microalbuminuria. Results Thirty‐five percent of patients were identified as having previously unrecognized hypertension, and 17% had pre‐hypertension (blood pressure greater than the 90th percentile but less than the 95th percentile). Fifty‐six percent of patients lacked the normal nocturnal dip in blood pressure. In addition, 21% had microalbuminuria, and their percent nocturnal dip was significantly less than those without microalbuminuria (P = 0.01). Conclusions Blood pressure abnormalities are common in adolescents with SCA and are a possible modifiable risk factor in the progression of sickle cell nephropathy. Pediatr Blood Cancer 2014;61:518–522. © 2013 Wiley Periodicals, Inc.